Perceived weight stigma in healthcare settings among adults living with obesity: A cross‐sectional investigation of the relationship with patient characteristics and person‐centred care - Paige I. Crompvoets; Anna P. Nieboer; Elisabeth F. C. vanRossum; Jane M. Cramm (Wiley, 2024)
Abstract Introduction Patients living with obesity often experience weight stigma in healthcare settings, which has worrying consequences for their healthcare experiences. This cross‐sectional study aimed to: (1) provide an overview of stigmatising experiences in healthcare settings reported by adults living with varying classes of obesity, (2) identify associations among patient characteristics and perceived weight stigma and (3) investigate the association between perceived weight stigma and person‐centred care (PCC). Methods Dutch adults living with obesity classes I (body mass index [BMI]: 30 to <35 kg/m2; n = 426), II (BMI: 35 to <40 kg/m2; n = 124) and III (BMI: ≥40 kg/m2; n = 40) completed measures of perceived weight stigma in healthcare settings and PCC. Descriptive, correlational and multivariate analyses were conducted. Results Of patients living with classes I, II and III obesity, 41%, 59% and 80%, respectively reported experiences of weight stigma in healthcare settings. Younger age, greater obesity severity and the presence of chronic illnesses were associated with greater perceived weight stigma. Greater perceived weight stigma was associated with lower PCC. Conclusion The results of this study emphasise the significant role of weight stigma in the healthcare experiences of patients living with obesity. Reducing weight stigma is expected to improve PCC and the overall quality of care for these patients. Minimising weight stigma will require efforts across various healthcare domains, including increasing awareness among healthcare professionals about sensitive communication in weight‐related discussions. Patient Contribution Our sample consisted of patients living with obesity. Additionally, patients were involved in the pilot testing and refinement of the PCC instrument.